The Role of Hematophagous Arthropods, Other than Mosquitoes and Ticks, in Arbovirus Transmission - Bradley J. Blitvich (Viruses, 2025)
Arthropod-borne viruses (arboviruses) significantly impact human, domestic animal, and wildlife health. While most arboviruses are transmitted to vertebrate hosts by blood-feeding mosquitoes and ticks, a growing body of evidence highlights the importance of other hematophagous arthropods in arboviral transmission. These lesser-known vectors, while often overlooked, can play crucial roles in the maintenance, amplification, and spread of arboviruses. This review summarizes our understanding of hematophagous arthropods, other than mosquitoes and ticks, in arboviral transmission, as well as their associations with non-arboviral viruses. Thirteen arthropod groups are discussed: bat flies, blackflies, cimicids (bat bugs, bed bugs, and bird bugs), Culicoides midges, fleas, hippoboscid flies, lice, mites, muscid flies (including horn flies and stable flies), phlebotomine sandflies, tabanids (including deer flies and horse flies), triatomines, and tsetse flies. Some of these arthropods are regarded as known or likely arboviral vectors, while others have no known role in arbovirus transmission. Particular attention is given to species associated with arboviruses of medical and veterinary significance. As the burden of arboviruses continues to grow, it is critical not to overlook the potential contribution of these lesser-known vectors.